2016
DOI: 10.1007/s11523-016-0444-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Therapeutic Potential of the Novel Isotype Specific HDAC Inhibitor 4SC-202 in Urothelial Carcinoma Cell Lines

Abstract: BackgroundTargeting of class I histone deacetylases (HDACs) exerts antineoplastic actions in various cancer types by modulation of transcription, upregulation of tumor suppressors, induction of cell cycle arrest, replication stress and promotion of apoptosis. Class I HDACs are often deregulated in urothelial cancer. 4SC-202, a novel oral benzamide type HDAC inhibitor (HDACi) specific for class I HDACs HDAC1, HDAC2 and HDAC3 and the histone demethylase LSD1, shows substantial anti-tumor activity in a broad rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 53 publications
5
68
0
Order By: Relevance
“…4SC‐202 is a novel small‐molecule inhibitor selectively targeting class I HDACs 1/2/3 and the lysine‐specific demethylase LSD1 . Notably, 4SC‐202 has shown excellent safety and promising anti‐leukemic activity in a recent phase I clinical trial (see TOPAS study at http://clinicaltrials.gov trial no.…”
Section: Resultsmentioning
confidence: 99%
“…4SC‐202 is a novel small‐molecule inhibitor selectively targeting class I HDACs 1/2/3 and the lysine‐specific demethylase LSD1 . Notably, 4SC‐202 has shown excellent safety and promising anti‐leukemic activity in a recent phase I clinical trial (see TOPAS study at http://clinicaltrials.gov trial no.…”
Section: Resultsmentioning
confidence: 99%
“…This broad specificity makes it difficult to interpret the results of inhibitor treatment in terms of precise biochemical mechanisms. Attempts have been made, with some success, to synthesize derivatives specific for individual HDACs and one such (a benzamide, 4SC‐202) is in a phase I clinical trial (Table ). However, the functional redundancy of HDACs, particularly class I enzymes , may reduce the clinical effectiveness of enzyme‐specific inhibitors.…”
Section: Hdaci Generally Inhibit Several Members Of the Hdac Familymentioning
confidence: 99%
“…The drug 4SC-202 has been shown to inhibit the growth of colorectal cancer cells, 38 hepatocellular carcinoma cells, 39 and urothelial carcinoma cells. 40 Here, it was demonstrated that 4SC-202 also blocks the growth of medulloblastoma cell lines, a cancer type with involvement of REST/ NRSF. 20,23 In conclusion, our system provides a toolbox for the expression of the central transcriptional repressor complex, CRC, allowing the complex to be assembled in a stepwise manner.…”
Section: Discussionmentioning
confidence: 89%
“…Accordingly, it was demonstrated that the drug efficiently inhibited both HDAC1 and LSD1 in the CRC isolates. The drug 4SC‐202 has been shown to inhibit the growth of colorectal cancer cells, hepatocellular carcinoma cells, and urothelial carcinoma cells . Here, it was demonstrated that 4SC‐202 also blocks the growth of medulloblastoma cell lines, a cancer type with involvement of REST/NRSF …”
Section: Discussionmentioning
confidence: 90%